Enjoyable learning media on respiratory disorders (ELGIPAS): Media to train students’ critical thinking - Rahmatin Ilmiatunnisa'; Yayuk Mulyati; Erti Hamimi; Rini Anggi Arista; H. Habbidin; Indra Fardhani (Universitas Muhammadiyah Malang, 2025)
Critical thinking is a key 21st-century skill but remains low in Indonesia, partly due to suboptimal learning media. In a Malang schools, 93% of students wanted more varied learning because lessons felt monotonous, underscoring the need for engaging media to support critical thinking. This study aimed to develop ELGIPAS (Enjoyable Learning Respiratory System Disorders) learning media that is valid, feasible, and effective in training students' critical thinking skills. This research used a R&D approach with the ADDIE model, incorporating interviews, questionnaires, and test data collection. As many as 31 eighth-grade students participated. Validation results showed the media achieved an 86% validity score and 92% material validity (very valid). The practicality and readability of ELGIPAS by teachers scored 100% and 99%, respectively. Student test scores increased significantly from a pretest average of 40.3 to a posttest average of 84.5, with a significance value of 0.000 (p < 0.05). The N-gain score was 0.732 (high), indicating substantial improvement. The highest increase was in the indicator of compiling alternatives (N-gain = 0.762), while evaluating arguments had the lowest increase (N-gain = 0.679). Thus, ELGIPAS is valid, practical, and effective for training students’ critical thinking in learning human respiratory system disorders.